2022
DOI: 10.12681/jhvms.29388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hempseed meal on performance, egg quality and egg yolk fatty acids content in laying quails

Abstract: In this study, the laying performance, external egg quality, egg yolk colour and fatty acids profile of quails (Coturnix coturnix japonica) fed on diets containing hemp seed meal (HSM) were determined. During 8 weeks trial, a total of 150, 10-weeks-old laying quails were used. Five diets were formulated to contain HSM at the level of 0 (control),5, 10, 15, and 20% that represented as 0 HSM, 5 HSM, 10 HSM, 15 HSM and 20 HSM, respectively.The performance parameters were not significantly (P>0.05)influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
4
2
Order By: Relevance
“…The lipids in the feed mixtures containing hemp and camelina cakes had 24.9% and 3.5 times, respectively, more ALA than in the feed mixture with rapeseed cake supplementation. The obtained results are consistent with the findings of other authors who enriched quail diets with n-3 PUFAs using flaxseed addition [ 11 , 51 , 52 ], hempseed meal and oil [ 7 , 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The lipids in the feed mixtures containing hemp and camelina cakes had 24.9% and 3.5 times, respectively, more ALA than in the feed mixture with rapeseed cake supplementation. The obtained results are consistent with the findings of other authors who enriched quail diets with n-3 PUFAs using flaxseed addition [ 11 , 51 , 52 ], hempseed meal and oil [ 7 , 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…A higher ( p < 0.01) albumen lightness was found in the rapeseed group compared to the camelina group. In the present study, the yolk and albumen lightness of quail eggs was higher than those reported by other authors [ 22 , 44 ]. However, colour depends not only on the composition of the object but also on its illumination environment and the angles of illumination and viewing [ 45 ].…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…The highest result was registered at W-28 and W-32 for HS-30% and HS-20% groups. Cufadar et al [ 26 ] reported that adding hemp seed meal to the diet of quails increases the albumen index. This result could be linked to the same bioactive components of HS, such as antioxidants, crude protein, and long-chain fatty acids that protect the magnum and uterus and promote albumin secretion in layers [ 27 ].…”
Section: Resultsmentioning
confidence: 99%